A crystal of time - Chainani, Soman (Chainani, Soman. School for Good and Evil, 2019)
"A false king has claimed the throne of Camelot, sentenced Tedros to death, and forced Sophie to be his queen. Only Agatha manages to escape. Now Agatha and the students at the School for Good and Evil must find a way to restore Tedros to his throne and save Camelot . . . before all of their fairy tales come to a lethal end"--OCLC.